Numériser les œuvres, renouveler les approches ? L’histoire de l’estampe à l’ère numérique - Johanna Daniel (Les Cahiers de Framespa)
This article proposes to reflect, through the specific case of prints, on the extent to which the digitisation of heritage is transforming research practices in art history. The massification of available reproductions, more and more often in HD, should not make us forget that only a small part of the collections is currently digitised. By exposing the digitisation practices and policies implemented by institutions, the aim is to provide keys for better understanding and exploiting the collections made available on the web. By questioning the changes in the relationship to the work that its reproduction implies, we will demonstrate the complementarity of physical and digital access to artefacts. Indeed, digitizations do not constitute a "neutral" double of the original, but tend to privilege the legibility of visual content to the detriment of indices of materiality. Finally, we'll look at how art historians handle these digital files: do the new possibilities offered by the screen interface have an impact on the way they write?